Study on the Ability of PCMSR to Produce Valuable Isotopes as a By Product of Energy Generation - Andang Widiharto (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2018)
PCMSR (Passive Compact Molten Salt Reactor) is a variant of MSR (Molten Salt Reactor) type reactors. The MSR is one type of the Advanced Nuclear Reactor types. PCMSR uses mixtures of fluoride salt if the liquid form is in a high temperature operation. The use of liquid salt fuel allows the application of on line fuel processing system. The on line fuel processing system allows extraction of several valuable fission product isotopes such as Mo-99, Cs-137, Sr-89 etc. The capability of MSR to produce several valuable isotopes has been studied. This study is based on a denaturized breeder MSR design with 920 MWth of thermal power and 500 MWe of electrical output power with the thermal efficiency of 55 %. The initial composition of fuel salt is 70 % of a mole of LiF, 24 % of a mole of 232ThF4, 6 % of a mole of UF4. The enrichment level of U is 20 % of a mole of U-235. The study is performed by a numerical calculation to solve a set of differential equations of fission product balance. This calculation calculates fission product generation due to fission reaction, precursor decay, and fission product annihilation due to decay, neutron absorption, and extraction. The calculation result shows that in quasi equilibrium conditions, the reactor can produce several valuable isotopes in substantially sufficient quantities, those are Sr-89 (0.3 kCi/MWth/day, Sr-90 (1,91 Ci/MWth/day), Mo-99 (1.7 kCi/MWth/day), I-131 (0.42 kCi/MWth/day), I-132 (0.782 kCi/MWth/day), I-133 (1.12 kCi/MWth/day), Xe-133 (11.8 Ci/MWth/day), Cs-134 (39.3 mCi/MWth/day), Cs-137 (2.32 Ci/MWth/day) and La-140 (1.05 kCi/MWth/day).